Synthesis, Characterization and Biological Evaluation of Novel Isoxazolo [5,4-b] Quinolines as potent Antimicrobial Agents (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
In order to combat antimicrobial resistance, antimicrobial chemotherapy made advances in the development of new potent antibiotics and antifungal agents. This is because the microorganisms are becoming resistant to the drugs due to improvements in current antibiotic classes by changing their pore formation mechanism and membrane permeability as well as by adjusting to combat the efficacy of the drugs. In order to address the microbial resistance, a series of novel isoxazolo [5,4-b] quinolines are synthesized and evaluated for antibacterial and antifungal activities. The synthesized compounds 4c, 4f and 4g exhibited potent antibacterial activity, and 4c and 4e revealed moderate antifungal activity.